Tendencies of Interaction between Russian Universities and Companies Implementing Innovative Development Programs. Reproductive Aspects - PASTUKHOV, Vladimir; KLIMAN, Nikolay; ALEKSEEV, Dmitry (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).24, 2018)
In this article, key indicators and trends of global innovative development are analyzed, and the role of the research and development sector in these processes is revealed. Attention is paid to the consideration of mechanisms of interaction between universities and state companies, concrete measures and steps of economic policy. The authors of the article analyze the real experience of the Russian economy at the present time. Based on the collected data on the total volume of R&D, revenues and the number of patents, regression models were constructed to determine the relationship between the named indicators. Based on the results of the analysis, recommendations on improving economic policy aimed at ensuring the achievement of goals and justifying the use of mechanisms of ‘compulsion to innovate’ in state companies are formulated.